A Convenient Representation of the Wealth Distribution and More Evidence on Homeownership and Wealth Inequality in Euro Area Countries - Martin Biewen; Stefan Glaisner; Rolf Kleimann (Institute of Labor Economics (IZA), 2021)
This note proposes a convenient graphical representation of the wealth distribution and illustrates it with data from the Eurosystem Household Finance and Consumption Survey (HFCS). We also present more evidence on the role of homeownership for wealth inequality in euro area countries.
Keywords: D31; C14; R3; 330; wealth inequality; transformation; homeownership